2019
DOI: 10.1186/s12883-019-1294-6
|View full text |Cite
|
Sign up to set email alerts
|

Michigan Neural Distinctiveness (MiND) study protocol: investigating the scope, causes, and consequences of age-related neural dedifferentiation

Abstract: Background Aging is often associated with behavioral impairments, but some people age more gracefully than others. Why? One factor that may play a role is individual differences in the distinctiveness of neural representations. Previous research has found that neural activation patterns in visual cortex in response to different visual stimuli are often more similar (i.e., less distinctive) in older vs. young participants, a phenomenon referred to as age-related neural dedifferentiation. Furthermor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…For example, using MR spectroscopy to quantify GABA concentrations in occipital voxels, Simmonite et al (2019) found that lower occipital GABA levels in older adults were associated with declines in fluid processing abilities. Furthermore, Chamberlain et al (2019;preprint) reported that individual differences in the category specificity of face versus house representations were linked to individual differences in VVC GABA concentrations in older adults, indicating a role of GABA in age-related neural dedifferentiation (see also Cassady et al, 2019;Gagnon et al, 2019;Lalwani et al, 2019). These findings substantiate the key role of proficient (particularly GABAergic) neuromodulation for high-fidelity (i.e., stable and distinct) neural representations and cognitive performance and lay the ground for future studies aiming to understand how agerelated deficits in neuromodulation are related to neural dedifferentiation across representational levels.…”
Section: Neural Dedifferentiation As a Consequence Of Age-related Neumentioning
confidence: 99%
“…For example, using MR spectroscopy to quantify GABA concentrations in occipital voxels, Simmonite et al (2019) found that lower occipital GABA levels in older adults were associated with declines in fluid processing abilities. Furthermore, Chamberlain et al (2019;preprint) reported that individual differences in the category specificity of face versus house representations were linked to individual differences in VVC GABA concentrations in older adults, indicating a role of GABA in age-related neural dedifferentiation (see also Cassady et al, 2019;Gagnon et al, 2019;Lalwani et al, 2019). These findings substantiate the key role of proficient (particularly GABAergic) neuromodulation for high-fidelity (i.e., stable and distinct) neural representations and cognitive performance and lay the ground for future studies aiming to understand how agerelated deficits in neuromodulation are related to neural dedifferentiation across representational levels.…”
Section: Neural Dedifferentiation As a Consequence Of Age-related Neumentioning
confidence: 99%
“…Older adults show greater prefrontal cortical activity during a wide range of motor tasks, including interlimb coordination tasks (Heuninckx et al, 2008) and steady-state walking (Chen et al, 2017;Mirelman et al, 2017;Hawkins et al, 2018). Whether age-related differences in prefrontal cortical activity play a beneficial (i.e., compensatory; Clark et al, 2019) or detrimental (i.e., age-related neural dedifferentiation; Payer et al, 2006;Gagnon et al, 2019) role in motor function in older adults remains controversial (for review see Seidler et al, 2010) and may depend on the context and challenge of the motor task (e.g., level of complexity and difficulty; Clark, 2015). In contrast to younger adults, older adults utilize motor control strategies that require higher levels of cognitive processing, which are effective at slower speeds but less effective during fast speed motor performance (Boisgontier and Nougier, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…compensatory) (Clark et al, 2019) or detrimental (i.e. agerelated neural dedifferentiation) (Gagnon et al, 2019;Payer et al, 2006) role in motor function in older adults remains controversial (for review see R. D. Seidler et al, 2010) and may depend on the context and challenge of the motor task (e.g. level of complexity and difficulty) (Clark, 2015).…”
Section: Introductionmentioning
confidence: 99%